Neuroimaging, Behavioral, and Gait Correlates of Fall Profile in Older Adults - Kirby, Krystal M.; Pillai, Sreekrishna; Brouillette, Robert M.; Keller, Jeffrey N.; De Vito, Alyssa N.; Bernstein, John P.; Van Gemmert, Arend W. A.; Carmichael, Owen T. (Frontiers in Aging Neuroscience, 2021)
Prior research has suggested that measurements of brain functioning and performance on dual tasks (tasks which require simultaneous performance) are promising candidate predictors of fall risk among older adults. However, no prior study has investigated whether brain function measurements during dual task performance could improve prediction of fall risks and whether the type of subtasks used in the dual task paradigm affects the strength of the association between fall characteristics and dual task performance. In this study, 31 cognitively normal, community-dwelling older adults provided a self-reported fall profile (number of falls and fear of falling), completed a gait dual task (spell a word backwards while walking on a GaitRite mat), and completed a supine dual task (rhythmic finger tapping with one hand while completing the AX Continuous Performance Task (AX-CPT) with the other hand) during functional magnetic resonance imaging (fMRI). Gait performance, AX-CPT reaction time and accuracy, finger tapping cadence, and brain functioning in finger-tapping-related and AX-CPT-related brain regions all showed declines in the dual task condition compared to the single task condition. Dual-task gait, AX-CPT and finger tapping performance, and brain functioning were all independent predictors of fall profile. No particular measurement domain stood out as being the most strongly associated measure with fall variables. Fall characteristics are determined by multiple factors; brain functioning, motor task, and cognitive task performance in challenging dual-task conditions all contribute to the risk of falling.